2020
DOI: 10.3390/biomedicines8120557
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Maternal Immune System in the Pathogenesis of Autism Spectrum Disorder

Abstract: Autism spectrum disorders (ASD) are a group of neurodevelopmental disorders characterised by impairments in communication, social interaction, and the presence of restrictive and repetitive behaviours. Over the past decade, most of the research in ASD has focused on the contribution of genetics, with the identification of a variety of different genes and mutations. However, the vast heterogeneity in clinical presentations associated with this disorder suggests that environmental factors may be involved, acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 143 publications
(268 reference statements)
1
19
0
Order By: Relevance
“…Early epidemiological studies produced conflicting results, but later studies focussed on serologically confirmed influenza cases using serum antibodies or other markers of inflammation and have provided additional evidence for maternal inflammation during development as a risk factor for schizophrenia ( Brown et al., 2004 ; Ellman and Susser, 2009 ; Scola and Duong, 2017 ). Similar associations have been described for autism risk ( Atladóttir et al., 2010 ; Jiang et al., 2016 ; Lee et al., 2015 ; Ornoy et al., 2015 ; Patterson, 2011 ; Ravaccia and Ghafourian, 2020 ; Zerbo et al., 2015 ). Whether a similar increase in neurodevelopmental diseases will occur in the years following SARS-CoV-2 emergence remains to be seen.…”
Section: Introductionsupporting
confidence: 80%
“…Early epidemiological studies produced conflicting results, but later studies focussed on serologically confirmed influenza cases using serum antibodies or other markers of inflammation and have provided additional evidence for maternal inflammation during development as a risk factor for schizophrenia ( Brown et al., 2004 ; Ellman and Susser, 2009 ; Scola and Duong, 2017 ). Similar associations have been described for autism risk ( Atladóttir et al., 2010 ; Jiang et al., 2016 ; Lee et al., 2015 ; Ornoy et al., 2015 ; Patterson, 2011 ; Ravaccia and Ghafourian, 2020 ; Zerbo et al., 2015 ). Whether a similar increase in neurodevelopmental diseases will occur in the years following SARS-CoV-2 emergence remains to be seen.…”
Section: Introductionsupporting
confidence: 80%
“…Comorbidity of two or more of these disorders is observed at rates higher than what it would be expected by chance, suggesting the existence of clusters of shared biological mechanisms ( 3 , 4 ). While cooccurrence of neurological features and conditions is frequently observed, very often, NDDs also include a variety of extra-neurological clinical signs such as hypotonia, dysmorphology, cardiologic or metabolic features, as well as gastrological problems such as constipation or diarrhea, which are specially frequent in ASD and ADHD ( 5 7 ), or immunological abnormalities ( 8 , 9 ). The recent advances in genotyping and sequencing technologies have propelled the identification of risk/causal genes, which has pointed to remarkable genetic heterogeneity among and within specific NDDs; for intellectual disability alone, pathogenic mutations in more than 1,000 genes have been confirmed in the SysID database (a systematic and manually curated catalog of ID-associated genes) ( 10 ).…”
Section: Introduction: Heterogeneity Beyond Idiopathic Neurodevelopmental Disordersmentioning
confidence: 99%
“…Maternal immune activation during pregnancy has also been comprehensively researched in order to better understand potential etiologies of autism. Infectious outbreaks, particularly the Rubella outbreak of the 1960s, provided substantial evidence that supported maternal immune activation as a risk factor for autism, proving that the disease caused but Rubella virus (and not the vaccine) is directly causing significant brain damage resulting in intellectual disability, autism and blindness [ 37 , 38 ]. Rubella infection is a hallmark of viral infection causing brain damage in the fetus and subsequent neurodevelopmental impairments including intellectual disability and autism.…”
Section: Immune System In Autismmentioning
confidence: 99%